Development of an Internet of Things-Based Scoreboard Learning Media for Mechatronics Control Technique Education - Fauzi, Yoyon; Sutopo, Yeri; Widjanarko, Dwi (Universitas Negeri Semarang, 2023)
This research is motivated by the need for students in the Electronics Engineering program to master technology that meets the demands of the workforce, one of which is the Internet of Things (IoT). However, based on observations and interviews with Control Engineering teachers at SMK Negeri 1 Bawang, this technology has not been optimally taught. Therefore, there is a need to develop IoT-based learning media. This study aims to develop an IoT-based scoreboard learning media, and to evaluate its feasibility, practicality, and effectiveness. The research employs the Research and Development method using the ADDIE model, which includes five stages: Analyze, Design, Development, Implementation, and Evaluation. Data were collected using media feasibility assessment sheets, material feasibility assessment sheets, product practicality questionnaires, and tests. The data analysis methods used in this study include (1) categorical analysis to determine the feasibility level of the learning media; (2) reproducibility and scalability coefficients to determine the practicality of the learning media; and (3) N-Gain to measure the effectiveness of the learning media. The results show that the developed learning media has a high level of feasibility. The practicality of the product was rated as practical based on user assessments. Additionally, the improvement in student learning outcomes, as indicated by the N-Gain scores, demonstrates that the learning media is effective for use.